Efikasi Insektisida Imidakloprid 25% terhadap Struktur Populasi (Myzus persicae SULZER) dan Musuh Alami pada Tanaman Cabai Merah (Capsicum Annuum L.) - I GEDE AGUS ADI WIRADARMA; KETUT AYU YULIADHI; DWI WIDANINGSIH (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2018)
Efficacy Insecticide Imidaklofrid 25% Against The Natural Enemy and Population Structure (Myzus Persicae SULZER) On Red Chili (Capsicum Annuum L) This study aims to determine the effect of insecticides made from Imidacloprid 25% active against the Myzus persicae pest population structure and natural enemies. The results showed that the treatment of insecticide Imidakloprid 25% had significant effect on the abundance of M. persicae, M. persicae density, and the abundance and diversity of natural enemies in red chili plant. The highest population abundance of M. persicae was found in the control treatment with an average of 7.24 and the lowest in the treatment dose of 200 g/ha with an average of 0.56 plants on ten leaves. Treatment of Insecticide Imidacloprid 25% also influenced the density of M. persicae, the highest density was found in the control treatment that was 0.23 head/m2 while the lowest was found in the treatment of insecticide dose 200 g/ha was 0.09 head/m2. Treatment Insecticide Imidakloprid 25% also affects the existence of natural enemies in chili planting. Found two types of natural enemies of the predator and parasitoid groups. From the predatory group Menochilus sexmaculatus and from the parasitoid group Aphidiid, the observed parasitoid is the mummi M. persicae. The highest abundance of natural enemies was found in the control treatment with an average of 11.55 while the lowest abundance at the treatment dose was 200 g/ha with an average of 3.14. Imidacloprid 25 % Insecticide also affects the diversity of natural enemies, the highest diversity was found in the control treatment of 0.14% while the lowest diversity was found in the 200 g/ha dose of insecticides treatment of 0.05%.